The Landscape of Business Growth for Oil and Gas Upstream Companies: A case from Japan - Matsubara, Fumihiko (International Journal of Energy Economics and Policy, 2019)
Why is Japan, the 4th largest oil consumer in 2016, unable to develop a globally competitive oil and gas upstream company? This paper suggests that the Japanese government should merge two oil companies, which are both under governmental control, Inpex and Japex. The analysis revisits the 2008 debate on strategies between CERA, an esteemed energy consulting company in the US, and a group of Japanese scholars. CERA suggested that Japanese energy companies should acquire a large equity stake upfront in new exploration projects and sell to new investors as the potential identified by exploration grows. Alternatively, a group of Japanese scholars suggests Japanese energy companies should acquire oil and gas upstream projects that are close to the end and adapt Japanese technology for increased and enhanced oil recovery. Desk research and interviews with four experts were conducted for this study and it was found that both strategies are necessary. Keywords: Japanese oil and gas upstream companies, Growth of business JEL Classifications: Q40, Q48 DOI: https://doi.org/10.32479/ijeep.8240